2021
DOI: 10.3389/fonc.2021.660615
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Prediction Model for Lymph Node Metastasis Based on a Molecular Panel and Clinicopathological Factors in Oral Squamous Cell Carcinoma

Abstract: ObjectiveLymph node metastasis is the most important factor influencing the prognosis of oral squamous cell carcinoma (OSCC) patients. However, there is no proper method for predicting lymph node metastasis. This study aimed to construct and validate a preoperative prediction model for lymph node metastasis and guide personalized neck management based on the gene expression profile and clinicopathological parameters of OSCC.MethodsBased on a previous study of related genes in OSCC, the mRNA expression of candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Bur et al [ 21 ] developed machine learning algorithms by using clinicopathologic data from 782 cT1-2N0 OSCC patients to predict pathologic nodal metastasis, they found the best classification performance was achieved with a decision forest algorithm (AUC = 0.840). Wang et al [ 22 ]. constructed a prediction model for nodal metastasis based on molecular panel and clinicopathological factors in 112 cN0 OSCC patients, the model with the combination of CDKN2A, PLAU, T stage and pathological grade was the best in predicting lymph node metastasis (AUC = 0.807).…”
Section: Discussionmentioning
confidence: 99%
“…Bur et al [ 21 ] developed machine learning algorithms by using clinicopathologic data from 782 cT1-2N0 OSCC patients to predict pathologic nodal metastasis, they found the best classification performance was achieved with a decision forest algorithm (AUC = 0.840). Wang et al [ 22 ]. constructed a prediction model for nodal metastasis based on molecular panel and clinicopathological factors in 112 cN0 OSCC patients, the model with the combination of CDKN2A, PLAU, T stage and pathological grade was the best in predicting lymph node metastasis (AUC = 0.807).…”
Section: Discussionmentioning
confidence: 99%
“…Nomograms have been widely used to predict survival outcomes in a variety of cancers, including OSCC, by reflecting the prognostic strength of relevant variables ( 13 ). Previous nomograms designed for OSCC mostly focused on the prognostic effect of genes, biomarkers, or specific subsite and tumor grade of OSCC ( 3 , 11 , 13 , 16 ). Recently, Zhou et al.…”
Section: Discussionmentioning
confidence: 99%
“…Nomograms have been widely used to predict survival outcomes in a variety of cancers, including OSCC, by reflecting the prognostic strength of relevant variables (13). Previous nomograms designed for OSCC mostly focused on the prognostic effect of genes, biomarkers, or specific subsite and tumor grade of OSCC (3,11,13,16). The current practice for OSCC management is largely directed by multidisciplinary discussions in tumor boards, which take into consideration the cancer stage, adverse pathological factors, individual patient factors, and the likely functional consequences and morbidity of each treatment approach (19).…”
Section: Discussionmentioning
confidence: 99%
“…There are also studies demonstrating the overexpression of CDKN2A in OSCC [ 28 , 29 ]. The Wang and others’ [ 30 ] analysis demonstrated that the expression of CDKN2A was upregulated in OSCC tissues compared with normal tissues in Oncomine database ( p -Value < 0.01). Furthermore, mRNA expression of the CDKN2A in HNSCC (head and neck squamous cell carcinoma) was upregulated compared with normal tissues in the GEPIA (Gene Expression Profiling Interactive Analysis) database ( p -Value < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mRNA expression of the CDKN2A in HNSCC (head and neck squamous cell carcinoma) was upregulated compared with normal tissues in the GEPIA (Gene Expression Profiling Interactive Analysis) database ( p -Value < 0.01). On the other hand, in the GEPIA database, a high expression of CDKN2A was associated with better survival in HNSCC patients ( p -Value < 0.05) [ 30 ]. The different results of the studies can be explained by differences in the pathogenesis of a subset of OSCCs [ 14 ].…”
Section: Discussionmentioning
confidence: 99%